2014
DOI: 10.1002/anie.201310597
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Tetrahexahedral Rhodium Nanocrystals with Extraordinarily High Surface Energy and High Electrocatalytic Activity

Abstract: Noble metal nanocrystals (NCs) enclosed with high-index facets hold a high catalytic activity thanks to the high density of low-coordinated step atoms that they exposed on their surface. Shape-control synthesis of the metal NCs with high-index facets presents a big challenge owing to the high surface energy of the NCs, and the shape control for metal Rh is even more difficult because of its extraordinarily high surface energy in comparison with Pt, Pd, and Au. The successful synthesis is presented of tetrahexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 43 publications
2
94
0
Order By: Relevance
“…Direct fuel cells have been recognized as a promising future power source due to advantages, including environmental aspects, facile storage, easy refilling and high power density1234567. However, the lack of active and durable anode catalysts has greatly limited the large-scale commercialization of direct fuel cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct fuel cells have been recognized as a promising future power source due to advantages, including environmental aspects, facile storage, easy refilling and high power density1234567. However, the lack of active and durable anode catalysts has greatly limited the large-scale commercialization of direct fuel cells.…”
mentioning
confidence: 99%
“…However, the lack of active and durable anode catalysts has greatly limited the large-scale commercialization of direct fuel cells. So far, platinum (Pt) has been considered as one of the best catalysts and exclusively utilized in fuel cells23456, but they suffer from high cost and poor carbon monoxide (CO) tolerance8910. Alloying Pt with less expensive oxophilic metals ( M ) such as gold (Au), silver (Ag) and especially nonprecious 3d transition metals11121314 is an effective route to improve CO tolerance and catalytic activity of catalysts, owing to the synergistic and electronic structure alteration mechanism15161718192021222324.…”
mentioning
confidence: 99%
“…For example, Yu et al . has shown that the convex Rh nanocrystals bound by {830} facets exhibit higher activity for ethanol electro-oxidation than irregular Rh nanoparticles, as well as commercial Rh black41. Huang and co-authors pointed out that wavy Rh nanowires have numerous structural defects/grain boundaries that are responsible for high catalytic activity42.…”
mentioning
confidence: 99%
“…Importantly, these catalysts exhibited remarkably different current density in the oxygen adsorption/desorption region (0.10-0.80 V). It is well-known that the low-coordinated atoms such as steps, kinks, or structural defects can greatly enhance the oxygen adsorption, thus resulting in large oxygen adsorption/desorption currents [31,40]. All the hyperbranched Rh triangle nanoplates showed larger oxygen adsorption/desorption currents than the commercial Rh black, with Rh branch-6:2 exhibiting the largest current value.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, Rh is an important functional material with excellent catalytic performances in a wide variety of important applications such as hydrogenation, hydroformylation, CO oxidation, NO x reduction, and fuel cell-related reactions [28][29][30][31]. In the last decade, great efforts have been made to improve the catalytic properties of this noble metal by tailoring the morphologies and surface structures of Rh NCs [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%